In vitro effects of intestinal microsymbionts on the cytokine production - O. V. Bukharin; E. V. Ivanova; I. N. Chaynikova; N. B. Perunova; I. A. Nikiforov; O. E. Chelpachenko; T. A. Bondarenko; A. V. Bekpergenova (Медицинская иммунология, 2023)
The most important role in homeostasis of intestinal immune belongs to the immunoregulatory properties of the microbiota which activates intracellular signaling systems, cytokine expression, production of protective factors and limits inflammatory reactions in the intestine by interacting with the pattern recognition receptors. The outcome of interactions between the microbiota and host cells (development of an inflammatory process or maintenance of intestinal homeostasis) depends on many factors, including a potential ability of intestinal commensals to influence the cytokine network in human body. Due to disturbances of quantitative and qualitative microbiota profile (dysbiosis), the cytokine balance may be changed by the influence of intestinal microsymbionts and their metabolites on immune and epithelial cells of intestines, thus contributing to the development of various human disorders. The aim of this study was to evaluate the immunoregulatory properties of eubiotic and dysbiotic human intestinal microsymbionts by assessing the effects of their cell-free supernatants on cytokine production in the in vitro system. The study was conducted on 49 eubiotic and 77 dysbiotic strains of microorganisms isolated from conditionally healthy patients examined for colon dysbiosis. To assess immunoregulatory properties of intestinal microsymbionts, we studied the effects of cell-free supernatants from bacterial and fungal cultures up on production of proinflammatory (IFNγ, TNFα, IL-17, IL-8, IL-6) and anti-inflammatory (IL-10, IL-1ra) cytokines secreted by mononuclear cells isolated from peripheral blood of healthy persons. The intestinal microbiota was determined by bacteriological methods. Identification of isolated microbial cultures was performed using MALDI TOF MS Microflex LT series (Bruker Daltonics, Germany). The level of cytokines was determined by enzyme immunoassay using commercial test systems (“Cytokine”, Russia). Statistical evaluation included discriminant analysis, classification decision tree and resultant mapping method. The multivariate statistical analysis enabled us to determine the range of the most informative indexes among cytokines and microbial cultures that changing their production in order to assess the state of homeostasis in eubiosis and intestinal dysbiosis. It was found that the supernatants of eubiotic cultures of intestinal symbionts exhibited a pronounced ability to inhibit the level of pro-inflammatory cytokines (IFNγ, IL-8) and to stimulate the secretion of anti-inflammatory cytokine (IL-10), whereas the dysbiotic cultures predominantly induced pro-inflammatory cytokines (IL-17, IFNγ, TNFα). In maintaining a uniform balance between pro- and anti-inflammatory cytokines during eubiosis, both associations of microsymbionts (in descending order of factor loads): Bacteroides spp. > E. coli > Lactobacillus spp.), and monocultures (Bifidobacterium spp. and Lactobacillus spp.) made a significant contribution via IL-10 induction. In cases of intestinal dysbiosis, we found an increased number of associations between microsymbionts inducing secretion of pro-inflammatory cytokines was. The pro-inflammatory profile of dysbiotic cultures was determined by the influence on IFNγ production (ranged in descending order of factor loads) of Bifidobacterium spp. > Enterococcus spp. > E. coli > Lactobacillus spp. associations, as well as S. aureus > Candida spp associations. The secretion of IL-17 was influenced by the monoculture of Clostridium spp., and by association C. acnes > S. aureus > Klebsiella spp. Monocultures of Bifidobacteria and Escherichia exerted effects upon TNFα production. Thus, during eubiotic state, the normobiota maintains a uniform balance of pro- and anti-inflammatory cytokines, and, in presence of intestinal dysbiosis, a shift in the balance of cytokines towards pro-inflammatory ones may occur due to increased levels of their secretion, an expanded spectrum of cytokines from this group, and increased number of single bacteria and associations of microbial cultures affecting their production.